PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, DAN LOCUS OF CONTROL, TERHADAP AUDIT JUDGMENT - Fenny Astari Kurnianingsih, 12.05.52.0155; Alfasadun, Alfasadun (Students Journal of Accounting and Banking, 2016)
This research aimed to examine the effect of obedience pressure, locus of control, and task complexity toward audit judgment that taken by auditor with auditorâs experience as a control variable. This research was carried out at the Central Java province with the respondent from auditors who work in Public Accountant Firms (KAP) in Semarang, Surakarta and Purwokerto. The sampling was conducted by purposive judgment sampling technique. The criterias are auditor who worked on the Public Accountant Firms (KAP) that listed on Compartment IAI Directory Public Accountant, has worked at least 1 year experience, and have education as a Bachelor. Data is collected using questionnaires distributed as 88 and only 68 questionnaires that can be processed. Data analysis using multiple linear regression method. The results of this study showed that the obedience pressure and task complexity have impact on audit judgment with negative direction, locus of control have positive effect on the auditors judgment audit Auditorâs experience as control variable have positive effect too on audit judgment, it is proved that auditorâs experience controlled the effect of independent variable to audit judgment.Keywords: Obedience Pressure, Task Complexity, Locus Of Control, Auditorâs Experience, Audit Judgment